Implementasi Sequential Search Pada Pencarian Data Tarif Aplikasi Perjalanan Dinas Karyawan PT Telkom Akses - Yaya Sudarya Triana; Anjar Rochana; Anindyka Elras Saputri (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
PT Telkom Access has rules on travel rates approved by the Board of Directors. Each unit has the budget to do the trip, budget travel agency would have taken into account by the party Finance. Budget travel agency includes the price of the accommodation, transport, taxis, money and pocket money. For this assignment the fare has not been run properly because swelling the budget cost of the trip. Therefore, this research will be made an application that implements the method of Sequential Search. Sequential Search methods are used to help find the data mapping rates that are already stored in the database, the data rates will be stored in the array which will then look for data rates in accordance with PT Telkom access employees level. The results of this research resulted in an application as a tool for searching a data rate of travel service, so that the budget can be managed properly.